Manuk Enterprise / Nasyarudin Piee... [et al] - Piee, Nasyarudin; Satar, Amirul; Vincent, Frazier Melai; Karon, Wilson Manjan (2010)
Business plans are “road map” for business creation. It’s meant “You identify your origin, select a destination, and plot the shortest distance between the two points”. In other word a business plan also known as a detailed blueprint for activities needed to establish a business for example details of product or service, the market for the product or service, and the management of the business providing that product or service. Besides that, business plans also the “Yardstick” by which a business owner measures success in meeting stated goals and objectives. Last but not least business plan is a tool for obtaining a loan from lending agency, or for attracting venture capital.We decided to name our company as MANUK ENTERPRISE which is form in partnership.Our business plan is focus on producing and selling CHICKEN. Apart of producing and selling chicken, we also selling the good varieties of collect and selling the chicken manure as organic fertilizer for the farmers.